2019
DOI: 10.1021/acs.iecr.9b02818
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Oxidative Degradation of Lignin-Based Phenolic Compounds in Batch Reactor

Abstract: Vanillin, vanillic acid, acetovanillone, syringaldehyde, syringic acid, and acetosyringone are products obtained from lignin oxidation in an alkaline medium. The evaluation of their individual degradation under oxidation conditions mimicking lignin oxidation is an important tool to better understand this reaction and maximize the yield of target value-added products. In this context, the main objective of the present work was to study the kinetics of degradation of the selected ligninbased phenolic compounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Meanwhile, the Cβ‐Cγ cleavage mechanism seems to be also slightly enhanced by the molecular oxygen. This assumption is corroborated by other studies and, therefore, the use of specific catalysts favoring the oxidation of the primary hydroxy group or novels strategies implying the selective pre‐oxidation of lignins could help to obtain enhanced yields of phenolic aldehydes from lignin when molecular oxygen is used as oxidant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the Cβ‐Cγ cleavage mechanism seems to be also slightly enhanced by the molecular oxygen. This assumption is corroborated by other studies and, therefore, the use of specific catalysts favoring the oxidation of the primary hydroxy group or novels strategies implying the selective pre‐oxidation of lignins could help to obtain enhanced yields of phenolic aldehydes from lignin when molecular oxygen is used as oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with the ones reported by Casimiro et al. in a recent study and confirms without any possible ambiguity the fundamental role of the molecular oxygen in the mechanisms bringing the instability of the phenolic monomers during the oxidative depolymerization of lignin.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of one or several process parameters on lignin oxidative depolymerization performed through batch experiments have been intensively investigated with the primary objective of achieving the ideal conditions for obtaining the maximum conversion of lignin while avoiding the oxidation of the phenolic monomers produced [ 8 , 41 , 43 , 47 , 48 , 54 , 55 , 59 ]. The origin, composition, and processing of lignin (pulping process, isolation method, pretreatment, etc.…”
Section: Oxidative Depolymerization Of Ligninmentioning
confidence: 99%
“…The origin, composition, and processing of lignin (pulping process, isolation method, pretreatment, etc. ), the oxygen partial pressure, the initial temperature, and the lignin and sodium hydroxide concentration in the reaction solution were studied, and its effect on the selectivity and efficiency of alkaline oxidative depolymerization process was evaluated [ 8 , 48 , 51 , 56 , 59 , 60 ]. It was found that a high partial pressure of oxygen reduces reaction time but leads to an increased rate of vanillin oxidation.…”
Section: Oxidative Depolymerization Of Ligninmentioning
confidence: 99%
See 1 more Smart Citation